2016
DOI: 10.3892/ijmm.2016.2613
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-205-5b inhibits HMGB1 expression in LPS-induced sepsis

Abstract: Inflammatory cytokines belonging to high mobility group box (HMGB)1 play a key role in sepsis through yet unknown mechanisms. The inflammatory response is modulated by microRNAs (miRNAs or miRs) at multiple levels and is poorly understood. In this study, the regulation of HMGB1 by miRNAs was evaluated using 3-(2,4-dimethoxybenzylidene)anabaseine (GTS-21) to activate the cholinergic anti-inflammatory pathway (CAP) and decrease HMGB1 expression in RAW264.7 cells. Microarray-based miRNA expression profiling of RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…Overexpression of miR-15a/16 in the LPS-treated murine macrophage RAW264.7 downregulated the expression of Toll-like receptor (TLR)4 and IL-1 receptor-associated kinase 1 (IRAK1), contributing to immunosuppressive phenotypes [53, 61]. Similarly, expression of miR-205-5b alleviates the expression of high mobility group box 1 (HMGB1) [62]. …”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of miR-15a/16 in the LPS-treated murine macrophage RAW264.7 downregulated the expression of Toll-like receptor (TLR)4 and IL-1 receptor-associated kinase 1 (IRAK1), contributing to immunosuppressive phenotypes [53, 61]. Similarly, expression of miR-205-5b alleviates the expression of high mobility group box 1 (HMGB1) [62]. …”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 is a nuclear transcription factor and it is also a late inflammatory mediator in the pathogenesis of sepsis and ARDS. HMGB1 mRNA is highly expressed in sepsis and mechanical ventilation‐induced lung injury in vivo (Wolfson, Mapes, & Garcia, ; Zhou, Wang, Li, LI, & SANG, ). Extracellular HMGB1 is mainly used as proinflammatory factors, involved in promoting inflammatory reactions, leukocyte aggregation, and other physiological processes, which can aggravate the progression of sepsis and acute lung injury (Entezari et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…29 Another group showed that the upregulation of miR-205-5b is a potential therapeutic target for the treatment of sepsis. 30 A variety of miRNAs such as miR-150, miR-15a/16, miR-132, miR-122, and miR-27a as biomarkers, were described in the context of sepsis. [31][32][33][34][35][36] Importantly, our results demonstrated differential expression of 36 upregulated and 20 downregulated miRNAs in HXC treatment group compared with SS rats.…”
Section: Mirna Proles Aer Hxc Treatmentmentioning
confidence: 99%
“…Zhou et al had showed that the upregulation of MicroRNA-205-5b as a potential therapeutic target for the treatment of sepsis. 26 Some evidence recently showed that the abnormal expression of miRNA is closely related with the occurrence and development of diseases. Therefore, the present study using high-throughput microRNA and metabolome expression proling method was conducted to investigate the metabolic mechanisms of HXC exerting its therapeutic effect in a model of SS.…”
Section: Introductionmentioning
confidence: 99%